Impact on equity prices of pronouncements related to nonpension postretirement benefits - Espahbodi, Hassan; Strock, Elizabeth; Tehranian, Hassan (Journal of Accounting and Economics, 1991)
This study examines the impact on equity prices of nine pronouncements related to the proposed accounting for nonpension postretirement benefits. Compared to a control group, the experiment firms exhibit significant negative abnormal returns around the issuance of the Exposure Draft on nonpension postretirement benefits. The negative abnormal returns are most pronounced for firms with few retirees relative to current employees, firms with high debt ratios, small firms, and firms currently reporting these benefits on the pay-as-you-go basis. These results are consistent with the contracting cost hypotheses.